A study on the adoption of IoT smart home service: using Value-based Adoption Model. (29th July 2017) - Kim, Yonghee; Park, Youngju; Choi, Jeongil
Abstract : This study aims to comprehensively examine the adoption of smart home service. A new model combining VAM (Value-based Adoption Model) and TAM (Technical Acceptance Model) was developed and analysed with a set of variables from Unified Theory of Acceptance and Use of Technology and Elaboration Likelihood Model. Perceived value was affected by both perceived benefit and perceived sacrifice. In particular, perceived benefit was found to have a strong positive effect on perceived value. In contrast, privacy risk and innovation resistance were found to limit perceived value. This study holds considerable significance as it proposes a new approach to IoT (Internet of Things)-based smart home service adoption using VAM and TAM. Through these two models, the study determined that it is imperative for businesses to constitute and secure appropriate infrastructure for residents to use IoT-based smart home service. Developing content related to security is also crucial.